«Вопиющіє безобразіє…»: позбавлення пенсії онуки О.С. Пушкіна - Марочко, В. (Проблеми історії України: факти, судження, пошуки, 2012)
Стаття висвітлює обставини позбавлення персональної пенсії М.В. Бикової — онуки О.С. Пушкіна, а також ставлення радянської влади до «колишніх поміщиків», дворян, офіцерів царської та білої армій. The article reveals the circumstances under which M.V.Bykova, a grand-daughter of Alexander Pushkin, was deprived a special retirement payment. It also provides the data on the attitude of the Soviet authorities towards the “former landlords”, aristocrats, and officers of the Tsar and the White Army.